2019
DOI: 10.3390/ijerph16081319
|View full text |Cite
|
Sign up to set email alerts
|

Health of Refugees and Migrants—Where Do We Stand and What Directions Should We Take?

Abstract: International migration, particularly to Europe, has increased in the last few decades, making research on aspects of this phenomenon, including numbers, challenges, and successes, particularly vital [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…other host or destination country). The 19 publications included one guideline and/or recommendation document by a professional international body 33 ; seven reports by the ECDC 12,[34][35][36][37][38][39] ; one WHO report 40 ; four systematic reviews [41][42][43][44] ; one review 45 ; three studies focusing on at least one aspect of migrants' sexual health with specific recommendations [46][47][48] ; two expert reviews of recommendations. 49,50 Characteristics of included publications are displayed in Table 2.…”
Section: R E Su Ltsmentioning
confidence: 99%
See 1 more Smart Citation
“…other host or destination country). The 19 publications included one guideline and/or recommendation document by a professional international body 33 ; seven reports by the ECDC 12,[34][35][36][37][38][39] ; one WHO report 40 ; four systematic reviews [41][42][43][44] ; one review 45 ; three studies focusing on at least one aspect of migrants' sexual health with specific recommendations [46][47][48] ; two expert reviews of recommendations. 49,50 Characteristics of included publications are displayed in Table 2.…”
Section: R E Su Ltsmentioning
confidence: 99%
“…While most of the studies mentioned previous experiences of violence among migrants, only two provided recommendations in relation to sexual violence, FGM screening and further support or treatment. 33,42 Nevertheless, evidence was not provided to support the recommendations. Other elements of sexual health and medical practice were highlighted in relation to minors, such as legal and ethical aspects (e.g.…”
Section: R E Su Ltsmentioning
confidence: 99%
“…It has to be indicated that, early trauma, separation from families, cultural shock and integration stress, difficulty in transferring credentials, language, financial reasons, legal status, lower self-esteem and resilience, stereotyping, and barriers to healthcare services, in addition to adverse working conditi1ons, might deteriorate physical and mental health (Ahonen, 2019;Keidar et al, 2019;Sweileh, 2018;Moyce and Schenker, 2018;Migration Policy Institute Europe, 2018). Furthermore, immigrant workers might face a greater risk of other key social determinants, such as poor housing or living conditions, which can contribute to the risk of other physical health and mental health outcomes (Hargreaves et al, 2019).…”
Section: Hypothesis 2b a Wage Lower Than The National Minimum Wage Might Be Associated With Deteriorated Mental Healthmentioning
confidence: 99%
“…Illegal immigration status, limited knowledge of the language, lack of confidence, poor employment relations knowledge, insecure employment conditions, lack of inspections, inexistence of health insurance and discrimination negatively affect immigrant s integration and well-being (Keidar et al, 2019;World Health Organization, 2018;Drydakis, 2017;Campbell and Price, 2016;Anderson, 2010). Meta-analyses indicate that immigrant workers bear a high burden of physical and 1 In this study, immigrant represents an umbrella term to refer to people of non-Greek origin who live in Greece who might have, or not have granted a permit to live and work in the state (Oxford Dictionary of English, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The identified goals have the purpose of limiting inequalities and implementing programs for the good management of migration, mobility, and integration; recent studies suggest that countries where integration is greater have better socio-economic and health outcomes [ 18 ].…”
mentioning
confidence: 99%